Pengaruh Tekanan dan Kesempatan dengan Identitas Moral Sebagai Pemoderasi Terhadap Perbuatan Menyontek - Efendri Efendri; Ludwina Harahap (LP. Ma'arif Janggan Magetan, 2024)
This research aims to analyze the influence of pressure and opportunities on cheating which is moderated by moral identity. The number of active students at the time this research was conducted in May 2020 was 2,218 people who made up the population. From this population, samples are taken that meet certain criteria (purposive sampling). The number of samples selected was 395 people. From the data obtained and then processed using the warpPls 8 application, the results showed that the variables pressure (X1) and opportunity (X2) had a significant effect on fraud (Y) with p_values ​​of <0.01 and <0.01 respectively. The moral identity variable (Z) significantly strengthens the relationship between the pressure (X1) and opportunity (X2) variables with cheating (Y) with each p-value <0.01. The moral identity variable (Z) does not significantly influence the cheating variable (Y) with a p_value of 0.06. The moral identity variable (Z) functions as a pure moderating variable.